2005
DOI: 10.1063/1.2133915
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic wave transmission through subwavelength metallic meshes sandwiched between split rings

Abstract: We report the extraordinary enhanced transmission of microwaves through a subwavelength metallic mesh sandwiched between two identical split-ring arrays. Such split-rings/metallic mesh/ split-rings structure demonstrates some unique electromagnetic ͑EM͒ characteristics. It is found that the transmittances of EM wave are significantly enhanced at some frequencies near the stop bands of the split rings. The theoretical simulation indicates that two different physical mechanisms dominate those transmissions: nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Zhou et al also investigated the effect of changing the air gaps between the layers of the structure to show tuning of the two individual modes. In addition Hou et al 16 have undertaken a study where subwavelength split ring resonators ͑SRRs͒ were fabricated around foam balls and held in an array orientated normal to the metal mesh. When subwavelength SRRs are arranged as an array, the combined response exhibits a large negative permeability over a narrow frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al also investigated the effect of changing the air gaps between the layers of the structure to show tuning of the two individual modes. In addition Hou et al 16 have undertaken a study where subwavelength split ring resonators ͑SRRs͒ were fabricated around foam balls and held in an array orientated normal to the metal mesh. When subwavelength SRRs are arranged as an array, the combined response exhibits a large negative permeability over a narrow frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…13 This effect is predictable using the transfer-matrix method (TMM) and has been reported in the literature utilizing various other structures. 7,[14][15][16] In order to determine the basic design steps for obtaining the desired response, the required transmission matrix for the structure is predicted using Jones calculus. It is assumed that the incident field is linearly polarized at an angle h with respect to the x-axis.…”
mentioning
confidence: 99%
“…This intriguing and counterintuitive (in view of the opaqueness of the single constituents taken alone) result motivated a growing interest in the transmission properties of heterostructures containing SNG materials, possibly combined with other type of materials, with a wide variety of extensions and generalizations proposed in the recent literature (Zhou et al, 2005;Hou et al, 2005;Guan et al, 2006;Fang and He, 2008;Kim and Lee, 2008;Feng et al, 2009;Oraizi and Abdolali, 2009;Castaldi et al, 2010Castaldi et al, , 2011aDing et al, 2010;Butler et al, 2011;Cojocaru, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, in Zhou et al (2005), Hou et al (2005) and Butler et al (2011), it was shown numerically and experimentally (at microwave frequencies) that, for an ENG slab sandwiched symmetrically between two identical DPS layers, total transmission (with phase delay) may occur under normal-incidence illumination.…”
Section: Introductionmentioning
confidence: 99%